Driving patterns, confidence, and perception of abilities following moderate to severe traumatic brain injury: a TBI model system study. (3rd July 2021) - Novack, Thomas A.; Zhang, Yue; Kennedy, Richard; Rapport, Lisa J.; Marwitz, Jennifer; Dreer, Laura E.; Goldin, Yelena; Niemeier, Janet P.; Bombardier, Charles; Bergquist, Thomas; Watanabe, Thomas K.; Tefertiller, Candice; et al.
ABSTRACT: Objective: Describe driving patterns following moderate-to-severe traumatic brain injury (TBI). Participants: Adults (N = 438) with TBI that required inpatient acute rehabilitation who had resumed driving. Design: Cross-sectional, observational design. Setting: Eight TBI Model System sites. Main Measures: A driving survey was completed at phone follow-up. Results: Most respondents reported driving daily, although 41% reported driving less than before their injury. Driving patterns were primarily associated with employment, family income, sex, residence, and time since injury, but not injury severity. Confidence in driving was high for most participants and was associated with a perception that the TBI had not diminished driving ability. Lower confidence and perceived loss of ability were associated with altered driving patterns. Conclusion: Most people with moderate-to-severe TBI resume driving but perhaps not at pre-injury or normal levels compared to healthy drivers. Some driving situations are restricted. The relationship between low confidence/perceived loss of ability and driving patterns/restrictions suggests people with TBI are exhibiting some degree of caution consistent with those perceptions. Careful assessment of driving skills and monitoring during early stages of RTD is warranted, particularly for younger, male, and/or single drivers who express higher levels of confidence.